Geografias de enunciação : o lugar a partir do índice de agenciamento da paisagem - Loureiro, Ana Carolina de Melo (2016)
Noticing the way one can be captured by a certain way of experiencing a place is the aim of this paper. As a consequence, we were interested in understanding the construction of the landscape as enunciation and assemblage, by articulating Rancière’s (2005) and Deleuze’s and Guattari’s (1995; 2003) philosophical foundations about the issues involving aesthetics, politics and language. In order to do this, we analyzed the city of Muqui in the state of Espírito Santo in Brazil, considering the role itshistoric site has in the city tourism, since it is presented as the biggest historic site, having 186 historic heritage buildings. Those properties are related to the period of great wealth in the 1920s and 1930s thanks to the coffee economy. The analytical procedures consist in collecting official and image discourses from the agents of enunciation: Google, National Historic and Artistic Heritage Institute (IPHAN), Department of Cultural Affairs of the State of Espírito Santo (SECULT), Ministry of Tourism, Newspapers, Muqui City Council and Muqui City Hall. Thereafter the datawas typified and categorized based on itsemission and the theme repetition. We analyzed considering the efficiency of the territorialization. Consequently, we elaborated a "hierarchy of the strengths" by observing the agents in relation to the spread of their enunciation and the main themes. To conclude the analysis, we mapped the experience capture flow by using the Assemblage Index, presented by QueirozFilho (2015), as a way to show the territorialization/deterritorialization processes. To express such strengths we made use of Goethe’s (1993) Theory of Colors,which considers the distinction between the warm colors and the cool colors. We concluded highlighting possible interventions in the language field which give visibility to new ways of feeling and experiencing. As a proposition, we pointed out the effectiveness of the writing as a possibility to express a sensitive experience of the landscape.